Chinese-style ceramics in East Africa from the 9th to 16th century: A case of changing value and symbols in the multi-partner global trade - Bing Zhao (Afriques)
In this case study dedicated to Chinese style ceramic sherds excavated from archeological sites in East Africa, we have made use of multiple approaches. First, from a local viewpoint, the density of Chinese style ceramic sherds at a site may be used as a measurement tool to evaluate the degree of its involvement in long distance trade. In concentrating on the analyses of regional and global contexts, we propose a tentative division of Chinese style ceramics found in East Africa according to four phases: phase I (ca. 800-950/80 CE), phase II (950/80-1220/50 CE), phase III (1220/50-1430/50 CE), phase IV (1430/50-1500/510 CE). Chinese-style ceramics travelled from the production sites in China and South-East Asia to East Africa, by passing successively from different regional networks, that formed the multi-partner global networks. Thus, the periodization of Chinese imports in East Africa appears to show that each phase appears to fall within a particular configuration of these successive trade networks.From the 12th century onwards, ceramics became the first Chinese exported goods in maritime trade. From the global context of Sino-Swahili trade, the inequitable nature of the cheap Chinese ceramics traded against highly valued African commodities should also be mentioned. Nevertheless, our study shows the powerful social symbolic of Chinese ceramics in the Swahili world. From the local lens, it is the phenomenon of a changing value of Chinese ceramics in the long-distance trade. Indeed the “exotic” character of Chinese style ceramics seems to have been intentionally valorized in cultural practices such as feasts. Consequently, these objects actively contributed to the expanding power of the merchant elite, who took full possession of it both materially and symbolically.